2022
DOI: 10.1002/acr.24815
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and Risk of Juvenile Idiopathic Arthritis: A Mendelian Randomization Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…These studies have revealed common genetic risk loci for oligoarticular JIA, polyarticular JIA, and psoriatic JIA. [ 46 , 47 ] Mendelian randomization studies have provided insights into identifying genetically causative variants for JIA, further unraveling the mechanisms underlying JIA susceptibility and associated outcomes. Moreover, MR studies have helped in understanding racial, ethnic, and geographical variations in JIA.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have revealed common genetic risk loci for oligoarticular JIA, polyarticular JIA, and psoriatic JIA. [ 46 , 47 ] Mendelian randomization studies have provided insights into identifying genetically causative variants for JIA, further unraveling the mechanisms underlying JIA susceptibility and associated outcomes. Moreover, MR studies have helped in understanding racial, ethnic, and geographical variations in JIA.…”
Section: Resultsmentioning
confidence: 99%
“…Por otro lado, Yi y col en el año 2022 ( Yi Wu , et al, 2022), mencionan que existen datos mecanicistas y epidemiológicos que respaldan la importancia de la vitamina D en la promoción de la salud ósea y la modulación del estado de la enfermedad en la artritis idiopática juvenil pero que se necesitan más estudios para aclarar la eficacia de los suplementos de la vitamina D en pacientes con AIJ, mientras que Clarke y col en el año 2023 (Clarke , et al, 2023), indican que en su estudio no se encontró una relación causal entre los niveles de vitamina D y la AIJ por lo cual indican que es poco probable que la suplementación con vitamina D a nivel poblacional reduzca la incidencia de la AIJ.…”
Section: Discussionunclassified
“…Instead, a study by Thorsen et al reported no association between serum 25(OH)D concentration at birth and the risk of JIA later in life [ 69 ]. Similarly, a recent Mendelian randomization study by Clarke and colleagues showed no causal relationship between serum 25(OH)D and JIA [ 70 ]. Even so, considering the immunomodulatory properties and potential immune-restoring effects of vitamin D discussed earlier, we aim to explore how it affects JIA treatment and outcomes.…”
Section: Vitamin D: Chemistry Metabolism Optimal Serum Concentration ...mentioning
confidence: 99%
“…Lower UVR exposure may increase JIA risk Thorsen et al (2017) [ 69 ] Case–control No significant association was found between 25(OH)D levels and the risk of JIA. No evidence that 25(OH)D levels around birth are linked to later JIA risk Clarke et al (2023) [ 70 ] Mendelian randomization No evidence indicating a causal relationship between genetically predicted 25(OH)D levels and the incidence of JIA. Lack of evidence suggesting that genetically predicted JIA causally affects 25(OH)D levels Nandi et al (2022) [ 72 ] Observational A significant negative correlation between the JADAS-27 score and serum vitamin D was confirmed.…”
Section: Vitamin D: Chemistry Metabolism Optimal Serum Concentration ...mentioning
confidence: 99%